Fire Mitigation Strategy in Densely Populated Settlements in the Kertosentono Area, Malang City - Aulia, Fakhita; Sufianto, Heru (Jurnal Mahasiswa Departemen Arsitektur, 2024)
The Kertosentono area is one of the dense residential areas around the campus in Malang City. The settlement around the campus is always growing every year which is filled with stalls and boarding houses. The denser the buildings in an area, the higher the potential for fire disasters to occur, if a fire occurs, the fire will quickly spread from one building to another so that it will be difficult to extinguish it. This study aims to determine the value of the level of risk posed in the event of a fire disaster in a dense settlement in the Kertosentono Area, Ketawanggede Village and formulate an appropriate fire mitigation strategy. The level of fire risk is reviewed through observation, measurement, and weighting analysis using parameters of building density, distance between buildings, number of building functions, range of water sources, area of open space, and accessibility. Data shows that the entire area is classified as high risk of fire disasters because of the very dense residential conditions reaching 93.8 units/ha accompanied by the lack of fire protection infrastructure in the area. Mitigation strategies are in the form of structural and non-structural mitigation. Structural mitigation directives are in the form of the use of fire-resistant materials, the provision of RTH at least 10% of the total area of the area, and the procurement of firefighting infrastructure in the area. Meanwhile, non-structural mitigation directives are focused on community preparedness when facing fire disasters so that they can act safely in fire situations.